Abitur und Abituraufsätze zwischen 1882 und 1972 Prüfungspraktiken, professionelle Debatten und Aufsatztexte - Kämper-van den Boogaart, Michael; reh, sabine; Schindler, Christoph; Scholz, Joachim (Verlag Julius Klinkhardt, 2023)
The contributions in this volume present key findings from the Leibniz Association-funded project "Abiturprüfungspraxis und Abituraufsatz 1882 bis 1972". On the basis of an extensive corpus of German Abitur essays processed in a digital research environment, examination practices were reconstructed and contextualised - supplemented by the analysis of further sources. Educational history, legal and administrative constellations as well as subject and writing didactic paradigms were analysed, opening up a historical view of the so-called supreme discipline of the Abitur examination, which is also currently asserting its role in the dispute over the conditions for obtaining the general higher education entrance qualification.